Value of breast MRI for patients with a biopsy showing atypical ductal hyperplasia (ADH). Issue 6 (10th March 2017) - Tsuchiya, Keiko; Mori, Naoko; Schacht, David V.; Sheth, Deepa; Karczmar, Gregory S.; Newstead, Gillian M.; Abe, Hiroyuki
Abstract : Purpose: To evaluate the diagnostic value of dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) for patients with atypical ductal hyperplasia (ADH) in predicting malignant upgrade. Materials and Methods: 3T DCE‐MRI was performed for 17 patients with ADH (median age 52, range 42–76) proven by stereotactic biopsy ( n = 15), and ultrasound‐guided biopsy ( n = 2) from January 2011 to April 2015. All patients underwent surgical excision after the MRI. Two radiologists prospectively reviewed the MRI to determine the presence or absence of suspicious findings at the site of biopsy, and evaluated the MR features of any lesion present according to the Breast Imaging Reporting and Data System (BI‐RADS) lexicon. MRI findings and clinical information were correlated with the final surgical pathology by multivariate analysis. Results: Nine of 17 lesions were upgraded to malignancy. MRI demonstrated suspicious nonmass enhancement (NME) at the site of biopsy in all upgraded patients. The median size was 19.5 mm (range, 9–44 mm). In the eight patients without upgrade, no enhancement ( n = 2), linear enhancement along the biopsy track ( n = 4), thin rim enhancement around hematoma ( n = 1), and a focal NME ( n = 1) were seen. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of MRI findings were 100, 87.5, 90, and 100%, respectively. Multivariate analysis revealed that the presence of suspicious enhancement on MRI was the most significant predictor of upgrade to malignancy ( P = 0.0006) Conclusion: Our study revealed a high NPV of DCE‐MRI for patients with ADH in terms of malignant upgrade at subsequent surgery. This suggests that patients with ADH without suspicious enhancement on DCE‐MRI might be followed with DCE‐MRI rather than undergoing surgical excision. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2017;46:1738–1747.